A Short Review on SPEEK-Based Direct Methanol Fuel Cell (DMFC) for Automotive Power Systems - Norazlianie, Sazali; M. F., Ghazali; Juhana, Jaafar; Wan Norharyati, Wan Salleh; Mohd Hafiz Dzarfan, Othman (Akademia Baru Publishing (M) Sdn Bhd, 2019)
This review paper is to explain the current technology of SPEEK-based direct methanol fuel cell (DMFC) for automotive power systems. These green technology devices have received worldwide recognition and the product prototype was successfully tested in house. The primary objective of the review is to explain the production of SPEEK-based DMFC for automotive power systems, replacing a petrol and diesel used in a currently commercialize car fuel. The other objective is to produce SPEEK-based DMFC which has been proven via lab scale analysis to have better performance than commercially available Nafion® membrane for DMFC. The SPEEK-DMFC is a noiseless, environmentally friendly device and possess longer lifetime compare to the available petrol or diesel currently available in petrol station.